2000
DOI: 10.1002/(sici)1097-0290(19961020)52:2<320::aid-bit12>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Application of high hydrostatic pressure for increasing activity and stability of enzymes

Abstract: Elevated hydrostatic pressure has been used to increase catalytic activity and thermal stability of α‐chymotrypsin (CT). For an anilide substrate, characterized by a negative value of the reaction activation volume (ΔV≠), an increase in pressure at 20°C results in an exponential acceleration of the hydrolysis rate catalyzed by CT reaching a 6.5‐fold increase in activity at 4700 atm (4.7 kbar). Due to a strong temperature dependence of ΔV≠, the acceleration effect of high pressure becomes more pronounced at hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

13
137
0
4

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 211 publications
(154 citation statements)
references
References 59 publications
13
137
0
4
Order By: Relevance
“…Van der Waals forces are presumably favoured by pressure since they tend to maximize the packing density, producing a reduction in volume of the protein 5,11 . Opposing effects of pressure and temperature on hydrophobic interactions and hydrogen bond formation have been put forward as possible explanations for pressure stabilization of proteins against thermal denaturation 3,35 . Mozhaev et al 35 hypothesized that at the initial step of thermal inactivation, a protein loses a number of essential water molecules, and this loss may give rise to structural rearrangements.…”
Section: Introductionsupporting
confidence: 84%
See 1 more Smart Citation
“…Van der Waals forces are presumably favoured by pressure since they tend to maximize the packing density, producing a reduction in volume of the protein 5,11 . Opposing effects of pressure and temperature on hydrophobic interactions and hydrogen bond formation have been put forward as possible explanations for pressure stabilization of proteins against thermal denaturation 3,35 . Mozhaev et al 35 hypothesized that at the initial step of thermal inactivation, a protein loses a number of essential water molecules, and this loss may give rise to structural rearrangements.…”
Section: Introductionsupporting
confidence: 84%
“…Mozhaev et al 35 hypothesized that at the initial step of thermal inactivation, a protein loses a number of essential water molecules, and this loss may give rise to structural rearrangements. High pressure may hamper this process owing to its favourable effect on hydration of both charged and nonpolar groups 11,35 .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, β-galactosidase from Kluyveromyces lactis was inactivated at high hydrostatic pressure and high temperature, and the stability of this enzyme at extreme conditions of pressure could be enhanced by appropriately adjusting ionic strength of the buffer solution used (Cavaille-Lefebvre and Combes, 1998). Mozhaev et al (1996) showed that catalytic activity and thermal stability of α-chymotrypsin increased at the hydrostatic pressure below 360 MPa and by the addition of glycerol. Over this pressure limit, however, pressure-induced denaturation of enzyme molecules was strongly favored.…”
Section: Methodsmentioning
confidence: 99%
“…However, local changes including the rearrangement of hydrophobic groups after exposure to surrounding medium and the dissolution of hydrophobic groups might also take place after the overall changes in the thermal inactivation at higher temperatures, which was represented by biphasic mode of thermal inactivation (Kim, 1992;Tsuboi et al, 1978). High-pressure treatment was likely to favor simple first-order reaction through retarded local changes due to the reduction in thermal inactivation of enzyme molecules (Katsaros et al, 2009;Mozhaev et al, 1996;Rupley et al, 1983). This is supported by the fact that biphasic mode of thermal inactivation of trypsin only occurred at 60℃ at 300 MPa.…”
mentioning
confidence: 92%
See 1 more Smart Citation